Analysis of Direct Torque Control of Industrial Drives using Zone-Shifting SVM - Vicky Jose; K. Vinoth Kumar; S.Suresh Kumar; Nithin.T. Abraham; Dona Maria Mathew (Institute of Advanced Engineering and Science, 2014)
Direct Torque Control of Induction Motor has gained popularity in industrial applications mainly due to its simple control structure from its first introduction in 1986. Here the direct torque control (DTC) of induction motor with zone shifting space vector modulation (SVM) has been done. It uses a simple phase current re-construction algorithm for three phase induction motor (IM).The phase current re-construction algorithm is done by using information from the current that is from the phases between the inverter and the induction motor. The proposed algorithm is robust and very simple. It uses the AC current to get the stator current for estimating the motor flux and the electromagnetic torque. By evaluating through the torque value and the current the controlling of induction motor is done. The simulation results are also given which supports the direct torque control strategy of the induction motor (IM).DOI: http://dx.doi.org/10.11591/ijpeds.v4i3.5641